Mediating Role of Psychological Maladjustment in Relation Between Dark Triad, Psychological Distress and Subjective Happiness of Pakistani Emerging Adults - Mushtaq, Asia; Inam, Ayesha; Najmussaqib, Arooj; Afshan, Anjum; Ermagan-Caglar, Eda (Frontiers in Psychology, 2022)
The transition from adolescence to adulthood is fraught with challenges that might have impacts in later life and personality development. Earlier research investigated Dark Triad traits in connection to emotional problems. The current study, on the other hand, focused on investigating the mediating role of psychological maladjustment in the relation of Dark Triad traits, psychological distress, and subjective happiness in emerging adults. A sample of 546 participants aged 18 to 25 years (M = 21.2 years) from Pakistan have participated to complete online survey. Standardized assessment tools were used to measure the targeted variables. Results indicated that Machiavellianism and psychopathy were positively associated with psychological distress, whereas narcissism appeared to be a nonsignificant predictor. Subjective happiness was positively associated with Machiavellianism and negatively associated with psychopathy. In addition, mediation analysis through Structural Equation Modelling (SEM) indicated that the Dark Triad traits (Machiavellianism and psychopathology), psychological distress, and subjective wellbeing was explained by psychological maladjustment. Implications and limitations are discussed.